The Methyltransferase AflSet1 Is Involved in Fungal Morphogenesis, AFB1 Biosynthesis, and Virulence of Aspergillus flavus - Liu, Yaju; Zhang, Mengjuan; Xie, Rui; Zhang, Feng; Wang, Sen; Pan, Xiaohua; Wang, Shihua; Zhuang, Zhenhong (Frontiers in Microbiology, 2020)
The filament fungal pathogen, Aspergillus flavus, spreads worldwide and contaminates several important crops. Histone posttranslational modifications are deeply involved in fungal development and virulence, but the biological function of the histone methyltransferase AflSet1 in A. flavus is still unknown. In the study, Aflset1 deletion strain was constructed through homologous recombination, and it was found that AflSet1 up-regulates hyphae growth, and promotes conidiation by sporulation regulation genes: abaA and brlA. It was also found that AflSet1 involves in sclerotia formation and AFB1 biosynthesis via sclerotia related transcriptional factors and orthodox AFB1 synthesis pathway, respectively. Crop models revealed that AflSet1 plays critical roles in colonization and AFB1 production on crop kernels. Lipase activity analysis suggested that AflSet1 affects fungal virulence to crops via digestive enzymes. Stresses tests revealed that AflSet1 is deeply involved in fungal resistance against osmotic, oxidative and cell membrane stress. The preparation of N_SET, SET domain deletion mutants and H988K mutant revealed that both domains play critical roles in fungal development and AFB1 production, and that H988 is very important in executing biological functions on morphogenesis and AFB1 synthesis. Subcellular location analysis revealed that AflSet1 is stably accumulated in nuclei in both spore germination and hyphae growth stages, even under the stress of SDS. Through immunoblot analysis, it was found that AflSet1 methylates H3K4me2 and me3 as well as H3K9me2. This study provides a solid evidence to discover the biological functions of histone methyltransferase in pathogenic fungi.